Modulation of liquid holdup along a trickle bed reactor with periodic operation - Ayude, María Alejandra (2007)
Temporal variations of the liquid holdup in a mini-pilot scale trickle bed reactor cold-mockup, induced by an ON-OFF liquid flow modulation strategy of operation, are explored at different axial positions. The reactor is packed with porous beads of γ - Al2 O3 and the liquid holdup is approximately estimated with a conductimetric technique, using probes that mimic the packing. The effects of the liquid and gas superficial velocities, the bed depth and the cycling parameters, cycle period and split, on the liquid holdup modulation are examined for a wide range of conditions. For slow and intermediate cycle periods, the liquid holdup time dependence observed during the dry period is represented by an exponential function. The characteristic value of the decay is correlated to the examined variables. The correlation allows reconstruction of the liquid holdup time dependence along the column.